Public participation in environmental decision-making: A water sector perspective - Sarpong Hammond Antwi; Caroline Gilleran Stephens; Alec Rolston; David Getty; Suzanne Linnane (Environmental and Sustainability Indicators)
Public participation in water governance and management has evolved significantly, with various institutions and measures established to enhance public input. This study employs a two-step qualitative approach, combining stakeholder perspectives with the International Association for Public Participation (IAP2) Spectrum and the Aarhus Convention as analytical frameworks. The findings reveal that public participation in decision-making and implementation processes remains a work in progress, with significant gaps in fully integrating public perspectives into water governance and management decisions. Drawing on international best practices and stakeholder insights, this study proposes targeted interventions to promote inclusive participation, including the integration of digital technologies to enhance accessibility and transparency while balancing digital and traditional engagement approaches. It also underscores the role of environmental and sustainability education in promoting long-term public commitment and shared responsibility.